Best Practices in Assessment in Journalism Programs. (March 2020) - Wao, Felix; Romano, Angela; Hardin, Marie
Journalism programs face many challenges today as they work to prepare students with the knowledge and skills to enter the ever-changing journalism industry. On one hand, programs need to determine whether students are learning the competencies their program designers have identified as essential to the field. On the other, students need to demonstrate the mastery of those skills before graduation. One of the best ways to measure these achievements is through the development and implementation of effective assessment processes. Syndicate 8 focused on this process.